Islamic Education Perspectives in The Digital Era Among Gen Z - Lathiefatul Aghniyah; Nurzamsinar Nurzamsinar; Sibawaihi Sibawaihi; Mesrawati Mesrawati; Lala Lala; Fatimah Fatimah (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
The development of digital technology has brought significant changes to various aspects of life, including education, particularly Islamic Religious Education (PAI). Generation Z, as a generation growing up amidst technological advancements, possesses distinctive characteristics, such as high digital adaptability, interactive learning patterns, and openness to global information. However, these conditions also present challenges in the form of low control over digital media use, a moral crisis, and a weakening of spiritual values ​​among the younger generation. This study aims to analyze the perspective of Islamic education in facing the development of the digital era in Generation Z, while also examining the role of digital technology in supporting the Islamic education process. The study used a library research method with a descriptive-qualitative approach through analysis of various literature sources, such as scientific journals, books, articles, and relevant research results. The results show that Islamic education plays a strategic role in shaping the character of Generation Z by strengthening moral values, spirituality, digital literacy, and religious moderation. In addition, the use of digital technology in Islamic education, such as e-learning, social media, and interactive learning platforms, can increase learning effectiveness when integrated with Islamic values. Therefore, Islamic education is required to be adaptive to technological developments without ignoring the basic principles of religion, so that it can produce a generation that is critical, creative, adaptive, and still has a strong Islamic identity in the digital era.